2015
DOI: 10.1542/hpeds.2014-0200
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Sedation After Administration of Oral Contrast: A Retrospective Cohort Study

Abstract: Children who received oral contrast up to 58 minutes before ketamine sedation had a higher rate of vomiting than those who did not receive oral contrast. We did not identify cases of clinical aspiration, and the incidence of hypoxia between the 2 groups was not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Procedural sedation is regularly performed in other settings in which fasting is frequently incomplete: cardiac catheterisation [80]; therapeutic abortions [81]; eye surgery [82][83][84][85]; and abdominal imaging in children who have first received oral contrast [86][87][88]. None of these settings have been identified as showing an increased aspiration risk.…”
Section: Absent Risk Factorsmentioning
confidence: 99%
“…Procedural sedation is regularly performed in other settings in which fasting is frequently incomplete: cardiac catheterisation [80]; therapeutic abortions [81]; eye surgery [82][83][84][85]; and abdominal imaging in children who have first received oral contrast [86][87][88]. None of these settings have been identified as showing an increased aspiration risk.…”
Section: Absent Risk Factorsmentioning
confidence: 99%
“…Some studies have found no apparent association between aspiration and noncompliance with fasting recommendations in children ( 56 , 57 ). In addition, fasting is regularly incomplete before procedural sedation in other settings, such as coronary interventions, oral contrast ( 58 ) and eye surgery ( 59 ), and no increased aspiration risk has been shown in the above settings. Given the low observed frequency of aspiration, fasting strategies in procedural sedation can reasonably be less restrictive ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed fasting duration beyond reported criteria [ 8 , 12 ]. Another recent study found that fasting duration was significantly related to adverse events, especially vomiting, although hypoxia was not [ 10 ]. A future study investigating the depth of sedation in more subjects would be valuable for understanding the relationship between fasting duration and adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most worrying adverse events associated with sedatives is tracheal aspiration of regurgitated food; therefore, guidelines suggest that sedatives or analgesics should be administered on an empty stomach [ 8 ]. However, although many institutions follow this guideline, several recent studies have reported that no association exists between preprocedural fasting state and adverse events from sedation [ 9 , 10 ]. In addition, the clinical policy of the American College of Emergency Physicians published in 2014 recommended proceeding with sedation in the ED regardless of the fasting state, since preprocedural fasting does not reduce the risk of vomiting or aspiration [ 11 ].…”
Section: Introductionmentioning
confidence: 99%